Compressive strength of elderly vertebrae is reduced by disc degeneration and additional flexion. (February 2015) - Maquer, Ghislain; Schwiedrzik, Jakob; Huber, Gerd; Morlock, Michael M.; Zysset, Philippe K.
Abstract: Computer tomography (CT)-based finite element (FE) models assess vertebral strength better than dual energy X-ray absorptiometry. Osteoporotic vertebrae are usually loaded via degenerated intervertebral discs (IVD) and potentially at higher risk under forward bending, but the influences of the IVD and loading conditions are generally overlooked. Accordingly, magnetic resonance imaging was performed on 14 lumbar discs to generate FE models for the healthiest and most degenerated specimens. Compression, torsion, bending, flexion and extension conducted experimentally were used to calibrate both models. They were combined with CT-based FE models of 12 lumbar vertebral bodies to evaluate the effect of disc degeneration compared to a loading via endplates embedded in a stiff resin, the usual experimental paradigm. Compression and lifting were simulated, load and damage pattern were evaluated at failure. Adding flexion to the compression (lifting) and higher disc degeneration reduces the failure load (8–14%, 5–7%) and increases damage in the vertebrae. Under both loading scenarios, decreasing the disc height slightly increases the failure load; embedding and degenerated IVD provides respectively the highest and lowest failure load. Embedded vertebrae are more brittle, but failure loads induced via IVDs correlate highly with vertebral strength. In conclusion, osteoporotic vertebrae with degenerated IVDs are consistently weaker—especially under lifting, but clinical assessment of their strength is possible via FE analysis without extensive disc modelling, by extrapolating measures from the embedded situation. Highlights: Finite element (FE) models of healthy/degenerated intervertebral discs are created. Their endplates are successively embedded in stiff material and bonded to the discs. Vertebral load and damage at failure are computed under pure compression and lifting. Osteoporotic vertebral bodies are weaker loaded via discs, especially under lifting. Regression equations identified against the embedded situation avoid disc modelling.